Microsleep as a Risk Factor for Unsafe Behavior: A Systematic Literature Review - Elga Alifqiah Ihsan; Hendra Djamalus (Journal of Social Research, 2026)
Microsleep is a brief, unconscious episode of sleep that reduces alertness and slows reaction time, potentially triggering unsafe behavior. This condition significantly contributes to workplace and traffic accidents, particularly in high-vigilance sectors. This study aims to identify groups vulnerable to microsleep and the forms of unsafe behavior resulting from it based on a systematic review of literature published over the past five years. A systematic literature review (SLR) was conducted on 23 national and international articles relevant to microsleep, safety behavior, and fatigue. Vulnerable groups include drivers, pilots, heavy industry workers, maritime workers, healthcare personnel, and patients with sleep or neurological disorders. The identified unsafe behaviors include loss of focus, delayed responses, poor decision-making, reduced safety compliance, and increased accident risk. Microsleep clearly triggers various forms of unsafe behavior among vulnerable populations. Integrated prevention strategies, such as fatigue management and strengthening the safety climate, are essential to reduce its impact on occupational safety.